The quality of translation results by Google translate and Microsoft translator in translating classical Arabic texts based on the translation of the book Matn Al-ghāyah Wat Taqrib by Faiz El Muttaqin - Fayruza, Aida Zavirah; Irhamni, Irhamni; Tohe, Achmad (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2020)
This study aimed to describe the quality of translations results by Google Translate and Microsoft Translator in translating classical Arabic texts based on the translation of the book Matn Al-Ghāyah wat Taqrib by Faiz El Muttaqin by looking at three aspects in the target language; accuracy, acceptability, and readability. The data of this study were analyzed using comparative qualitative research methods. The results showed that Google Translate got a better score than Microsoft Translator. However, both of them produced inaccurate, unacceptable and illegible translations because machine translation cannot properly communicate the meaning and dynamics of the source language into the target language.